2021
DOI: 10.7554/elife.69317
|View full text |Cite
|
Sign up to set email alerts
|

Reduced antibody cross-reactivity following infection with B.1.1.7 than with parental SARS-CoV-2 strains

Abstract: Background: The degree of heterotypic immunity induced by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) strains is a major determinant of the spread of emerging variants and the success of vaccination campaigns, but remains incompletely understood.Methods: We examined the immunogenicity of SARS-CoV-2 variant B.1.1.7 (Alpha) that arose in the United Kingdom and spread globally. We determined titres of spike glycoprotein-binding antibodies and authentic virus neutralising antibodies induced by B.1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 30 publications
1
26
2
Order By: Relevance
“…Cele et al 29 also showed that B.1.351 infection generated better cross-neutralizing activity against earlier viral variants. These findings contrast with Faulkner et al 48 , who observed a large decrease in cross-neutralization of WT virus in B.1.1.7-infected individuals. However, Faulkner et al 48 used sera collected at around 11 days POS and, as discussed above, cross-neutralizing activity probably develops over time.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…Cele et al 29 also showed that B.1.351 infection generated better cross-neutralizing activity against earlier viral variants. These findings contrast with Faulkner et al 48 , who observed a large decrease in cross-neutralization of WT virus in B.1.1.7-infected individuals. However, Faulkner et al 48 used sera collected at around 11 days POS and, as discussed above, cross-neutralizing activity probably develops over time.…”
Section: Discussioncontrasting
confidence: 95%
“…To counter such mutations and their attendant antigenic changes, vaccines using the spike proteins from these variants of concern (VOCs) are under investigation 44 – 47 . Whether the variant spike proteins will elicit a robust neutralizing response with superior cross-neutralizing activity against parental strains and newly emerging variants has not been extensively studied 29 , 48 , 49 . Natural infection provides an important opportunity to compare the neutralizing antibody titres and cross-neutralizing activity generated from individuals exposed to different spike variants and will give insights into the antigenic distance between spike variants, thereby informing the design of second-generation vaccine candidates based on VOCs.…”
Section: Mainmentioning
confidence: 99%
“…However, in recent weeks, there has been a resurgence of SARS-CoV-2 cases in Israel. It is important to understand to what extent this resurgence is due to the high infectiousness of the delta variant(Chakraborty et al, 2021), lower protection of the vaccine against the delta or other variants as compared to the original strain(Faulkner et al, 2021; Martínez-Flores et al, 2021), or decreasing levels of anti-SARS-CoV-2 antibodies against all strains in vaccinated individuals(Israel et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…To improve vaccine efficacies and boost mucosal immunity against current and future SARS-CoV-2 variants researchers and vaccine companies are already investing the development of second-generation vaccines using diverse strategies. Interestingly, studies have shown that, in contrast to the early Wuhan-1 virus isolate or the Alpha variant, antibodies elicited in response to the Beta variant exhibit potent cross-reactivity as demonstrated by the binding and neutralization of S proteins from the Beta and P.1 variants, which emphasizes use of the Beta variant spike as a seed antigen for the next generation of vaccines [197,198]. Hence, Biontech, CureVac and AstraZeneca have designed a second-generation vaccine based on the Beta-variant S protein mutations.…”
Section: Discussionmentioning
confidence: 99%